Industrial subcontracting linkages in the Lagos region, Nigeria (2001)
This paper analyses the pattern of subcontracting linkages in the Lagos region within the contemporary held views of integration and industrial linkages. The paper shows that whether in terms of the number or volume, the spatial distribution of subcontracting varied markedly amongst the industrial estates/areas. Whereas subcontractors and subcontracting were found to be concentrated in just a few of the industrial estates/areas, subcontracting was identified in both intra- and inter-estates/areas. Considerable variation in production subcontracting linkages in terms of the number of flows became more complex in successive years.